Effects of caloric restriction diet on endothelial function in obese adults - Ghetti, Fabiana de Faria (2014)
Obesity is a chronic inflammatory disease characterized by excessive accumulation of fat in adipose tissue. Pathophysiological components due to excess of body fat, such as changes in the balance of adipokines, insulin resistance and increased inflammatory mediators, promote endothelial dysfunction and consequently higher risk of morbidity and mortality from cardiovascular causes. On the other hand, energy reduced diet has been recommended as non-pharmacological measure for treatment of obesity. Therefore, the aim of this paper was to realize a literature review on the effects of energy reduced diet on endothelial function in obese adults. Twenty-six papers with descriptions energy reduced diet, calorie restriction and weight loss, combined with the terms vasodilatation and endothelium, published in Medline and Scielo electronic databases were evaluated. It was noted that energy reduced diet, when it results in weight loss, changes metabolic, inflammatory, hemodynamic and neurovascular parameters, with restoration of normal endothelial function in obese subjects. However, to achieve those benefits, the energy reduced diet should be individualized, balanced and with guidance and prescription of experts.